Identification of artesunate as a specific activator of ferroptosis in pancreatic cancer cells - Eling, Nils; Hazin, John; Hamacher-Brady, Anne; Brady, Nathan (Oncoscience, 2015)
Oncogenic KRas reprograms pancreatic ductal adenocarcinoma (PDAC) cells to states which are highly resistant to apoptosis. Thus, a major preclinical goal is to identify effective strategies for killing PDAC cells. Artesunate (ART) is an anti-malarial that specifically induces programmed cell death in different cancer cell types, in a manner initiated by reactive oxygen species (ROS)-generation. In this study we demonstrate that ART specifically induced ROS- and lysosomal iron-dependent cell death in PDAC cell lines. Highest cytotoxicity was obtained in PDAC cell lines with constitutively-active KRas, and ART did not affect non-neoplastic human pancreatic ductal epithelial (HPDE) cells. We determined that ART did not induce apoptosis or necroptosis. Instead, ART induced ferroptosis, a recently described mode of ROS- and iron-dependent programmed necrosis which can be activated in Ras-transformed cells. Co-treatment with the ferroptosis inhibitor ferrostatin-1 blocked ART-induced lipid peroxidation and cell death, and increased long-term cell survival and proliferation. Importantly, analysis of PDAC patient mRNA expression indicates a dependency on antioxidant homeostasis and increased sensitivity to free intracellular iron, both of which correlate with Ras-driven sensitivity to ferroptosis. Overall, our findings suggest that ART activation of ferroptosis is an effective, novel pathway for killing PDAC cells.
Gesehen am 09.07.2020